Enhancing English Vocabulary Through Popular Song-Based Learning Experiences For The Eighth Grade Students - Annisa Fitriyatul Maghfiroh; Nur Hidayat; Dyah Nugrahani (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study investigates the effectiveness of integrating popular English songs as a medium for improving vocabulary mastery among eighth-grade students. The research was carried out at SMP Negeri 32 Semarang, involving 32 students from class VIII-B. A one-group pretest-posttest design was applied, allowing the researcher to evaluate the students’ vocabulary mastery before and after the given treatment. The treatment involved two learning sessions utilizing the song “Blue” by Yung Kai, implemented through structured and interactive song-based learning activities. Data collection was carried out through pre-tests and post-tests that assessed both receptive and productive vocabulary knowledge. The results showed a significant improvement in students’ vocabulary mastery, as the mean score increased from 62.19 (pre-test) to 85.69 (post-test). A paired sample t-test analysis using SPSS 26.0 confirmed a statistically significant difference with a p-value of 0.000. These findings suggest that using popular songs in English instruction is an effective strategy to support vocabulary development, student engagement, and retention of language in a meaningful and enjoyable context.